Effectiveness of computed tomography perfusion imaging in stroke management - Cviková, Martina; Haršány, Michal; Vinklárek, Jan; Štefela, Jakub; Fojtová, Iva; Mikulík, Robert (Frontiers in Neurology, 2024)
Objectives Current guidelines do not support the use of computed tomography perfusion (CTP) in stroke, except when identifying the penumbra during an extended treatment window. Therefore, this study aimed to define the yield of CTP in diagnosing a stroke diagnosis beyond the imaging of the penumbra in the hyperacute phase (0–6 h) and an extended time window (6–24 h). Materials and methods All consecutive patients with acute onset of symptoms within a 24-h window underwent CTP imaging. The diagnostic value of CTP was calculated against the clinical and radiological diagnoses of stroke. A positive CTP result was determined by the presence of either a core or penumbra on the RAPID summary. Clinical diagnoses corresponded to discharge diagnoses of stroke. A radiological diagnosis was established if early ischemic changes [Alberta Stroke Program Early CT Score (ASPECTS) <10] were observed on the baseline CT scan, acute infarction was confirmed on follow-up imaging, or symptomatic occlusion was evident on baseline CTA. Results Between November 2018 and November 2019, 585 consecutive patients with an acute neurological deficit underwent multimodal CT imaging. A total of 500 patients (85%) were included, where 274 (55%) were within the hyperacute phase, 153 (31%) had a radiological diagnosis of stroke, and 122 (24%) had a clinical diagnosis of stroke. CTP yielded positive results only in patients with a confirmed stroke (positive predictive value and specificity of 100%). When CTP results were negative, 43% of the cases turned out to stroke mimics. Patients with stroke mimics were younger (66 ± 17 vs. 73 ± 13) and had lower scores on the National Institutes of Health Stroke Scale [median 0; interquartile range (IQR) 0–2 vs. median 4; IQR 2–6] compared to patients with CTP-negative strokes. Conclusion In our study, CTP consistently indicated brain ischemia; therefore, in stroke management, CTP is most beneficial when it yields a positive result. A positive CTP result should prompt adequate stroke management actions without any delay. Conversely, a negative CTP result necessitates the consideration of both stroke and non-stroke diagnoses.